2022
DOI: 10.15406/paij.2022.06.00268
|View full text |Cite
|
Sign up to set email alerts
|

Utilization from ultraviolet to infrared light for CO2 reduction with P4O10/TiO2 photocatalyst

Abstract: This study aims to extend the light spectrum which could be absorbed by TiO2 to infrared ray light (IR) by loading P4O10 in order to promote the CO2 reduction performance of TiO2 photocatalyst. Three ranges of light with P4O10/TiO2 film are studied, which are ultra violet light (UV) + visible light (VIS) + IR, VIS + IR, and IR only. This study also investigates the impact of molar ratio of CO2/H2O or CO2/NH3 on the CO2 reduction characteristics of P4O10/TiO2 film. The largest CO2 reduction performance in case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…The measurement accuracy of the thermocouple used in the authors' previous study [15] was 0.1 • C. In addition, the temperatures, which were measured for 10 min using the thermocouple [15], were applied in this study. In this study, the illumination time of the Xe lamp for the photocatalytic CO 2 reduction experiment was 8 h, which was in keeping with the authors' previous studies [12][13][14][15]. According to the authors' previous work, the formation rate of CO attains its maximum value at approximately 2 h of Xe illumination and decreases gradually.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The measurement accuracy of the thermocouple used in the authors' previous study [15] was 0.1 • C. In addition, the temperatures, which were measured for 10 min using the thermocouple [15], were applied in this study. In this study, the illumination time of the Xe lamp for the photocatalytic CO 2 reduction experiment was 8 h, which was in keeping with the authors' previous studies [12][13][14][15]. According to the authors' previous work, the formation rate of CO attains its maximum value at approximately 2 h of Xe illumination and decreases gradually.…”
Section: Resultssupporting
confidence: 85%
“…In previous studies [12,13], the authors prepared P 4 O 10 /TiO 2 , which successfully extended the absorbed wavelength of light up to IR. Under IR illumination, the largest molar quantity of CO per unit weight of photocatalyst for the P 4 O 10 /TiO 2 film in the case of CO 2 /H 2 O was 2.36 µmol/g, while that in the case of CO 2 /NH 3 was 33.4 µmol/g [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Hierarchical ZnIn 2 S 4 nanorods, prepared using the solvothermal method, exhibited the production performance of CO of 54 µmol/g and CH 4 of 9 µmol/g [25]. According to the authors' previous studies [26], P 4 O 10 /TiO 2 has been investigated. The largest molar quantity of the CO per unit weight of the photocatalyst for P 4 O 10 /TiO 2 film in the case of CO 2 /H 2 O was 2.36 µmol/g under the light illumination condition with IR, while that in case of CO 2 /NH 3 was 33.4 µmol/g [26].…”
Section: Introductionmentioning
confidence: 99%
“…Cu is a promising dopant for expanding the light absorption to VIS since many previous studies have reported its good performance [13][14][15][16][17][18]. In addition, P 4 O 10 is also a promising dopant to expand the light absorption to IR since previous studies carried out by authors have reported its good performance [26]. However, there is no study to clarify the impact of the combination of the photocatalyst absorbing the light with VIS as well as that with IR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation